PENENTUAN CELAH PITA KATALIS ZnO/ZEOLIT YANG DISINTESIS DENGAN METODA SONIKASI - Fikriandini, Nabila; Khair, Miftahul (CHEDS: Journal of Chemistry, Education, and Science, 2023)
This study aims to determine the ZnO/Zeolite photocatalyst synthesis process with variations of ZnO/Zeolite 5%, 10%, 15%, 20%, and 25%. This research aims to determine the band gap of the ZnO/Zeolite catalyst. The method used in synthesizing ZnO/Zeolite photocatalysts is the sonication method with time variations of 15 minutes, 30 minutes, 45 minutes, and 60 minutes. ZnO/Zeolite photocatalysts were characterized with FTIR instruments to determine functional groups and the band gap energy values of ZnO/Zeolite catalysts using UV-DRS (Ultraviolet Diffuse Reflectance Spectroscopy) instruments. Based on UV-DRS data analysis using the Kubelka-Munk method, the bandgap energy data for each catalyst were obtained as follows 2.34 eV; 2.32 eV; 2.13 eV; 2.21 eV; and 2.22 eV.